أثر استراتيجيتي ( عباءة الخبير وافعل ولا تفعل ) في تحصيل مادة قواعد اللغة العربية عند طالبات الصف الاول المتوسط - عبد علي زيدان رنا (Journal of College of Education, 2020)
Current research aims to know the impact of their (mantle of the expert and do’s) in the collection of Arabic grammar material when students first grade average. Zahra minor girls-a province of application experience, sample consisted of (93), (31) student in the first pilot group that studied according to strategy (expert cloak), and (32) student in the experimental group II examined as a strategy (do’s and 30) control group student examined in accordance with the usual method, formulated a researcher (53) a behavioral objective, promised three sets of Mycobacteria research plans on according to strategy (expert cloak), strategy (do’s), and the usual way. The researcher examined the three research groups (first and second pilot, pilot officer), and prepared a test took over characterized by honesty and constancy, the number of paragraphs (40) paragraph. The researcher has applied the achievement test post on three research groups members (first and second pilot, pilot officer) and use appropriate statistical methods to analyze search results that showed the superiority of the second experimental group students studied under the strategy (do’s Two students) ]first experimental study according to strategy (expert cloak) and officer examined according to the normal way [ in Collection.